Evaluasi Usability Pada Website Sekolahkoding.com Dengan Menggunakan Metode Usability Testing dan Human Centered Design - Katon Pratama Susanto; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Sekolahkoding.com is a website that provides a variety of programming languages ​​using video material. The purpose of using the sekolahkoding as an evaluation is because seen from the similar web, the sekolahkoding has fewer visitors when compared to similar websites. Preliminary research conducted at SMKN 5 Malang and SMKN 12 Malang, there are several problems on the website, namely users have difficulty finding material, users are still not fluent when using the website, the display on the grid can be widened further, the display is less attractive, the display is less varied, the interaction needs to be simplified, the color buttons are emphasized even more, the server error when logging in. The purpose of this research is to get the results of testing usability from the schoolkoding.com website. The method used in this research is the first Usability Testing to evaluate the design of the coding school before and after the design improvement. The second method used is Human Centered Design for guidelines for designing the interface solution for the website sekolahkoding.com. In the tests carried out there are success parameters in three aspects, namely aspects of effectiveness, aspects of efficiency, and aspects of satisfaction. The results obtained in this aspect are the first aspect of effectiveness which is divided into three categories, namely Success in the initial design gets a score of 67% while the solution design gets a value of 100%, Non Critical Error in the initial design gets a value of 20.8% while in the solution design got a value of 0%, Critical Error in the initial design got a value of 11.8% while the solution design got a value of 0%. Furthermore, the efficiency aspect gets an increase of 219%. Then in the satisfaction aspect, the average score increase in the initial design scored 50 with the category Non Acceptable and grade F with "OK" information, while the solution design got a score of 77.5 with the category Acceptable and grade C for "Good".